Electronic Signals and Systems : Analysis, Design and Applications - K̲h̲ān, Muḥammad Nāṣir (River Publishers series in signal, image and speech processing., 2020)
The Book is intended for a course on signals and systems at the senior undergraduate level. The authors consider all therequirements and tools used in analysis and design of discrete time systems forfilter design and signal processing.